MENGGAMBAR TERSTRUKTUR MENURUNKAN TINGKAT HALUSINASI PASIEN GANGGUAN JIWA - edi sukamto; Rivan Firdaus; Tilka Asyaratun Kaamilah; Tomi Ihsan Muhaafidhin (MNJ (Mahakam Nursing Journal), 2022)
Introduction : Schizophrenia is mental disorders that indicated by hallucination. One of the method to make decressed level of hallucination the patien is by doing the positive activities like drawing therapy. This study aim to know the influence of the structured drawing therapy to decressed of hallucination level in ward of Punai RSJD Atma Husada Samarinda. Method : This study is case studies by intervention. The number of Population are 16 people and selected to be 4 people as sample by sampling technique is probability sampling by simple random sampling. Result : Before conducting the structured of drawing therapy, the subject A has 3 signs symptoms (21.4%), Subject B had 2 signs symptoms (12.2%), Subject C had 4 signs symptoms (28.5%) and Subject D has 1 sign symptoms (7.14%). After conducting the same application is not found sign and symptom of hallucination on Subject. Conclusion : The structured of drawing therapy influences to decressed of hallucinations. Recommendation :This therapy can be applied to decressed the Hallucination level to Patien who suffer the mental disorder where they can express their feelings through image media. Keywords : Drawing Therapy, Hallucinations